2016
DOI: 10.7903/ijecs.1404
|View full text |Cite
|
Sign up to set email alerts
|

Fixation and Recall of Youtube Ad Banners: An Eye-Tracking Study

Abstract: Attaching an ad banner on a clip in a video-sharing website such as YouTube has become common although eye-tracking studies have concluded that this fails to secure visitors' attention. To date, there have been no studies verifying whether ad banners on a video clip can ensure eye fixation from viewers. Through eye-tracking, this study investigates whether YouTube visitors fixate on ad banners, what the correlations between fixation duration on banners and overall fixation counts are, and the extent to which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
1
5
0
1
Order By: Relevance
“…Conversely, recall data were obtained using a poststimulus question, without the assistance of the brand. Only 8-10% of the subjects were able to remember two of the three brands shown in the experiment and this is a relatively low percentage (Tangmanee, 2016), but in agreement with previous studies in online environments (Hamborg, Bruns, Ollermann, & Kaspar, 2012). This comparison should be made with caution, as the methods, environments, and areas are different.…”
Section: Conclusion and Recommendationssupporting
confidence: 89%
See 1 more Smart Citation
“…Conversely, recall data were obtained using a poststimulus question, without the assistance of the brand. Only 8-10% of the subjects were able to remember two of the three brands shown in the experiment and this is a relatively low percentage (Tangmanee, 2016), but in agreement with previous studies in online environments (Hamborg, Bruns, Ollermann, & Kaspar, 2012). This comparison should be made with caution, as the methods, environments, and areas are different.…”
Section: Conclusion and Recommendationssupporting
confidence: 89%
“…These results are further supported by an analysis of the heat maps and the scan path, in which we observe that the subjects dedicate short periods of time to the processing of the sponsor. This lack of attention could be due to the overload of information present in the poster (Tangmanee, 2016). These results can be seen by the placement of the sponsor in the lower part of the poster as well.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…This study used an eye-tracking device to record and analyze participants' eye movement data. Many scholars have already used this device to examine Internet scanning behavior (Harrar, Le Trung, Malienko, & Khan, 2018;Lee & Ahn, 2012;Tangmanee, 2016), evidence that it is an effective method. All participants joined the experiment and signed a form indicating that they permitted the eye movement data collected.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, although some users continue to experience webpages with ads included, they report mentally skipping or filtering out the ads themselves -often resulting in a phenomenon dubbed banner blindness [17] or ad avoidance [42] -where ads are seemingly ignored, at least, from the advertiser's point of view. However eye-tracking studies have shown that users often continue to fixate on ads [62], and even without direct gaze ads would still lie in a user's peripheral vision, which may result in being implicitly processed [64]. Consequently, this paper aims to investigate whether so-called banner blindness is truly blind, and explores the main research questions of: How do ads affect: (1) user search performance; (2) search behaviours; and (3) user experiences, given an everyday search task.…”
Section: Introductionmentioning
confidence: 99%